Pengaruh Pembayaran Digital terhadap Konsumsi Rumah Tangga dengan PDB dan Inflasi sebagai Variabel Moderasi - Nabila Maharani Zaen; Aniek Hindrayani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of digital payments on household consumption with Gross Domestic Product (GDP) and inflation ada moderating variables. Data analysis is conducted using regression with Ordinary Least Square (OLS) estimation method. The research employs as quantitative approach utilizing secondari data obtained from the World Bank. The population of this study comprises all countries worldwide with the sample consists of 101 countries selected through convenience sampling. The results indicate that: (1) Digital payment variables have a positive and significant effect on household consumption. (2) GDP and inflation do not act as moderating variables that strengthen the relationship between digital payments and household consumption.